PERMASALAHAN PENYESUAIAN PERKAWINAN PADA ISTRI PRAJURIT ANGKATAN LAUT - Nurlita Endah Karunia; Srisiuni Sugoto; Sri Wahyuningsih (Fakultas Psikologi Universitas Hang Tuah, 2019)
A Couple in early marriage, should be able to adjust each of their expectation, roles, traits, and family of origin. Navy’s wives have to encounter a set of marital adjustment that different from the other couple in general because the cycle of deployment and reunion of their husband. This study aims to describe marital adjustment problems of navy’s wives and factors that contribute to marital adjustment. This is quantitative and qualitative study, using dyadic adjustment scale, psychological tests, and interview methods that processed using statistic and thematic. These participants are navy’s wives, length of married is below five years, and their husband experienced deployment cycle. The results of this study are participants have a marital adjustment problems in general and marital adjustment problems about deployment-reunion cycle that affected by factor personality and irrational expectancy. System support are needed for navy’s wives and family to reduce the negative effects during the deployment. Prepare program before married that consist psychologist aspects are needed to anticipate marital adjustment problems for navy’s wives